PENGARUH EFIKASI DIRI DAN BIMBINGAN KARIR TERHADAP KESIAPAN KERJA SISWA KELAS X DAN XI SMK NEGERI DI JAKARTA - Zain, Nuryetty; Marsofiyati; Jeniar , Ramadhanty (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2020)
This study aims to determine whether there is an effect of self-efficacy and career guidance on work readiness of class X and XI students at one of SMK Negeri in Jakarta. The research method used was a survey method. The population in this study is 499 students and the sample is 202 students. Data on work readiness (Y), self-efficacy (X1), and career guidance (X2) are primary data using a Likert scale. The data analysis technique used is the first measurement of the outer model consisting of individual reliability with a result greater than 0.7 (> 0.7). Construct reliability with results greater than 0.7 (> 0.7). The composite reliability value is greater than 0.6 (> 0.6). AVE value is greater than 0.5 (> 0.5). The second measurement of the inner model consists of r2 with a value of 0.871. Then, f Square Self-Efficacy (X1) with a value of 0.594 and Career Guidance (X2) with a value of 0.477. Whereas the VIF value is smaller than (<5.00) so there is no multicollinearity problem. Self-efficacy coefficient (X1) of 0.808 and t statistics is 17.493> 1.971 with a p-value of 0.00 <0.05. Career Guidance Coefficient (X2) of 0.151 and t statistic that is 2.776> 1.971 with a p-value of 0.00 <0.05.